2020
DOI: 10.1016/j.jacbts.2020.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil Deficiency Promotes Aberrant Repair and Adverse Remodeling Following Acute Myocardial Infarction

Abstract: Visual Abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 38 publications
1
49
2
1
Order By: Relevance
“…Eosinophils also secrete IL-4, cytokine playing an essential role in differentiation of macrophages towards M2 phenotype, and regulating myocardial tissue regeneration ( 53 , 54 ). Eosinophilic cationic protein mEar1 together with IL-4 was able to inhibit apoptosis is cardiomyocytes and prevent adhesion of neutrophils to endothelial wall, improving cardiac dysfunction ( 49 ).…”
Section: Eosinophilsmentioning
confidence: 99%
See 1 more Smart Citation
“…Eosinophils also secrete IL-4, cytokine playing an essential role in differentiation of macrophages towards M2 phenotype, and regulating myocardial tissue regeneration ( 53 , 54 ). Eosinophilic cationic protein mEar1 together with IL-4 was able to inhibit apoptosis is cardiomyocytes and prevent adhesion of neutrophils to endothelial wall, improving cardiac dysfunction ( 49 ).…”
Section: Eosinophilsmentioning
confidence: 99%
“…Eosinophilic cationic protein mEar1 together with IL-4 was able to inhibit apoptosis is cardiomyocytes and prevent adhesion of neutrophils to endothelial wall, improving cardiac dysfunction ( 49 ). Most likely production of IL-4 is a key feature providing beneficial effects of eosinophils during AMI, as injection of the recombinant IL-4 to eosinophil-deficient mice rescued adverse remodeling of the left ventricle after the permanent ligation of the left coronary artery ( 54 ). However, the potency of treatment with IL-4 appeared to be time-dependent: administration of IL-4 lost its efficiency when injected at the advanced stages of the post-MI remodeling ( 55 ).…”
Section: Eosinophilsmentioning
confidence: 99%
“…Notably, ΔdblGATA mice had a higher number of pro-inflammatory neutrophils and macrophages. Moreover, the expression of CD206, a marker for macrophage activation was reduced in ΔdblGATA mice but restored by intra-peritoneal eosinophil replenishment 70 . This clearly demonstrates the importance of eosinophils in inflammatory resolution.…”
Section: Eosinophils Help To Establish An Anti-inflammatory Environmentmentioning
confidence: 97%
“…However, functional studies have yet to assess the impact of these cells on regeneration. Interestingly, treatment of ΔdblGATA mice with IL-4 complexes, which are typically stored within pre-formed eosinophil granules, successfully rescued the adverse cardiac remodelling observed in these mice 70 . IL-4 mediated activation of macrophages is associated with a wound-healing phenotype.…”
Section: Eosinophils Help To Establish An Anti-inflammatory Environmentmentioning
confidence: 99%
“…Eosinophils are an understudied immune cell population in the ischemic heart. It was recently shown that eosinophil depletion worsened cardiac outcomes after permanent coronary artery occlusion, indicating this immune cell population warrants further investigation [26].…”
Section: Myeloid Cell Activity After Myocardial Infarctionmentioning
confidence: 99%